A Common Generalization of Dirac's Two Theorems - Carlen M. Mosesyan; Zhora G. Nikoghosyan (Изд-во НАН РА)
A theorem is proved including Dirac's two well-known theorems (1952) as particular cases.
Keywords: Mathematics; Graph theory